Analisis Perlakuan Akuntansi Terhadap Aset Bersejarah Berupa Bangunan dan Kereta Lori di PT Madubaru Yogyakarta Menurut PSAP 07 Tahun 2022 - Arif Rifanto; Citra Ayudiati (AKUNTANSI 45, 2025)
Heritage assets are assets with special treatment because they have heritageal value apart from their useful value. The accounting treatment of heritageal assets is not very highlighted and many heritageal assets are recorded as they are in accounting applications. The purpose of this study was to determine the suitability of the accounting treatment procedures (recognition, valuation, and presentation) of heritageal assets of buildings and lorry trains at PT Madubaru with Government Accounting Standard Number 07 of 2022. The research method used in this study uses a qualitative method with a descriptive approach. The results show that the accounting treatment (recognition, valuation, and presentation) of heritageal assets of buildings and lorry trains at PT Madubaru with PSAP (Government Accounting Standards Statement) Number 07 of 2022 is appropriate. PT Madubaru in the accounting treatment uses the PSAK (Statement of Financial Accounting Standards) reference, but it is still the same as PSAP (Government Accounting Standards Statement) Number 07 of 2022.